Impact of Foaming Agent: Water Ratio on Foam Stability of Lightweight Concrete - Prajapati, Abhilasha; Kumar, Rajesh; Maiti, Soumitra; lakhani, Rajni; Yadav, Amit (ASCEE, 2024)
Foamed concrete, renowned for its lightweight nature and thermal insulating properties, has gained substantial interest in the construction industry. The stability of foamed concrete is directly related to the stability of preformed foam used for making foamed concrete. Foam stability is the prime factor which influences the overall performance and properties of the foamed concrete. Foam stability refers to the ability of the foam to maintain its structure and volume over time. The stability of foamed concrete is greatly impacted by the selection of the foaming agent and the ratio of foaming agent to water (FA/W). Protein based foaming agent (as per ASTM C796/C796M-19) has been used for this study. An excess of water can weaken the foam structure, leading to instability, while inadequate water can lead to issues such as reduced workability and uneven distribution of foam within the mixture. This paper investigates the effect of FA:W ratio on the stability of foam concrete. Three different FA:W ratio i.e. 1:10, 1:20 and 1:30 has been used for this study. Respective slumps to these ratios have also been investigated at different time intervals to check their consistencies. Three mix proportions were used to produce foam concrete of 1000kg/m3 density. Impact of aforementioned FA/W ratios on the properties of foamed concrete (As per; IS 2185 part-4) were discussed in this article.